Islamic Religious Education Based on Inter-Religious Tolerance at the Elementary School - Susari Susari; Upiyani Upiyani; Marzuki Marzuki; Asrowi Asrowi; Rumbang Sirojudin; Wasehudin Wasehudin; Ita Cahyawati (Ta'dib, 2024)
Religious tolerance is a key value in multicultural societies, and schools are often a suitable place to build understanding and respect for diverse religious beliefs. In the context of education, Islamic Religious Education has an important role in shaping attitudes of tolerance between religious communities. This research aims to develop an effective Islamic Religious Education learning strategy in shaping the character of religious tolerance. This involves curriculum development, teaching methods, and relevant approaches. This study used a qualitative research approach with a phenomenological approach. The methodology of this research involved distributing a prepared questionnaire regarding inter-religious tolerance attitudes in elementary schools. Involving surveys, interviews, observations, documentation, and data analysis then providing a detailed description of the data collected. The steps in conducting research with a phenomenological approach, namely determining the location and individuals, data collection techniques, data recording procedures, field issues, and data storage stages. The results of this study show that (1) the curriculum design integrates tolerance values. (2) educators consistently incorporate teachings about toleration between religious groups into their teaching materials (3) educators serve as role models by symbolizing a tolerant lifestyle, and (4) organize significant religious events and community activities to further promote tolerance.